Status Sosial Orang Tua Mempengaruhi Kemandirian Anak - Ahmad Baidowi (LP2M Sekolah Tinggi Agama Islam Ar-Rosyid Surabaya, 2019)
Many people are very easy to give up on the grounds that Allah SWT. Has determined his fate like that. Fate cannot be avoided, because it is a provision of Allah SWT. Humans never know what will happen tomorrow, so that it doesn't happen as they don't want it, the family environment is the first and foremost place for children, to give influence and support to the development and growth of children. In this case, it is the family that first fills the personality / laying the foundation for the formation of the child's personality. Parents unplanned have instilled the habits they have so that the child becomes independent